2017
DOI: 10.3389/fphar.2017.00234
|View full text |Cite
|
Sign up to set email alerts
|

Management of Benign Prostatic Hyperplasia: Could Dietary Polyphenols Be an Alternative to Existing Therapies?

Abstract: The incidence of benign prostatic hyperplasia (BPH) is gradually on the increase. While conventional drugs such as the α1-adrenergic receptor antagonists and 5α-reductase inhibitors have been found to be useful in the treatment of BPH, the adverse side effects associated with their usage, have led to increased search for alternative means of managing this disease. Furthermore, although surgery has also been suggested to be a sure method, the cost and risks associated with it excludes it as a routine treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 99 publications
1
28
0
Order By: Relevance
“…Also, the mix of polyphenols from tomatoes and olive vegetation water can certainly contribute to the anti-inflammatory properties of the WTFS [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the mix of polyphenols from tomatoes and olive vegetation water can certainly contribute to the anti-inflammatory properties of the WTFS [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The constituents of QLX include numerous polyphenols and polyphenolic metabolites such as caffeic acid, gallic acid, p ‐coumaric acid, protocatechuic acid, neochlorogenic acid and chlorogenic acid. Dietary polyphenols are known to benefit management of BPH and CNP 35‐37 . The evidence suggested that QLX exerts a prostatic protective function and might be used to relieve LUTS associated with CNP and BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the mix of polyphenols from tomatoes and olive vegetation water can certainly contribute to the anti-in ammatory properties of the WTFS [43,44].…”
Section: Discussionmentioning
confidence: 99%